Periostin promotes chronic allergic inflammation in response to Th2 cytokines - Masuoka, Miho; Shiraishi, Hiroshi; Ohta, Shoichiro; Suzuki, Shoichi; Arima, Kazuhiko; Aoki, Shigehisa; Toda, Shuji; Inagaki, Naoki; Kurihara, Yuichi; Hayashida, Sayaka; Takeuchi, Satoshi; Koike, Kenta; et al. (The Journal of clinical investigation, 2012)
Allergic inflammation triggered by exposure of an allergen frequently leads to the onset of chronic inflammatory diseases such as atopic dermatitis (AD) and bronchial asthma. The mechanisms underlying chronicity in allergic inflammation remain unresolved. Periostin, a recently characterized matricellular protein, interacts with several cell surface integrin molecules, providing signals for tissue development and remodeling. Here we show that periostin is a critical mediator for the amplification and persistence of allergic inflammation using a mouse model of skin inflammation. Th2 cytokines IL-4 and IL-13 stimulated fibroblasts to produce periostin, which interacted with αv integrin, a functional periostin receptor on keratinocytes, inducing production of proinflammatory cytokines, which consequently accelerated Th2-type immune responses. Accordingly, inhibition of periostin or αv integrin prevented the development or progression of allergen-induced skin inflammation. Thus, periostin sets up a vicious circle that links Th2-type immune responses to keratinocyte activation and plays a critical role in the amplification and chronicity of allergic skin inflammation.